2015
DOI: 10.3758/s13414-015-1037-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring handedness asymmetries in the Simon effect

Abstract: Spatially corresponding stimulus-response pairings usually produce shorter reaction times (RTs) than do noncorresponding pairings, even when the spatial dimension of the stimulus is irrelevant to the task. This BSimon effect^for visual stimuli and manual responses is often larger for the stimulus location on the side to which the person's dominant hand is operating. The present study aimed at replicating and examining the nature of this asymmetry. To determine whether the Simon effect asymmetry is a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 41 publications
4
17
1
Order By: Relevance
“…The authors of the above-cited studies proposed that the Simon effect asymmetry is due to an attentional bias toward the operating space of the dominant effector, which results in stronger coding of the stimulus location in the visual hemifield. Seibold, Chen, and Proctor (2016) replicated this pattern of results for the location-based Simon effect but not for a wordbased Simon effect, for which the irrelevant location information is conveyed by the centered words left and right (Luo & Proctor, 2019). For right-handers responding to stimuli in physically left and right locations, Seibold et al found faster responses for the right hand than the left hand overall, and provided evidence that the apparent Simon effect asymmetry is an artifact of this difference in response hand/location.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…The authors of the above-cited studies proposed that the Simon effect asymmetry is due to an attentional bias toward the operating space of the dominant effector, which results in stronger coding of the stimulus location in the visual hemifield. Seibold, Chen, and Proctor (2016) replicated this pattern of results for the location-based Simon effect but not for a wordbased Simon effect, for which the irrelevant location information is conveyed by the centered words left and right (Luo & Proctor, 2019). For right-handers responding to stimuli in physically left and right locations, Seibold et al found faster responses for the right hand than the left hand overall, and provided evidence that the apparent Simon effect asymmetry is an artifact of this difference in response hand/location.…”
Section: Introductionmentioning
confidence: 77%
“…Reaction time We excluded trials with RTs above 900 ms and below 100 ms (2.5%), as well as error trials (3.4%) for the analysis of the RT, like Seibold et al (2016) and Rubichi and Nicoletti (2006) did. An analysis of variance (ANOVA) was conducted on RT with stimulus location, response location, and effector as within-participants factors on RT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations